ANALISIS KEMAMPUAN LITERASI MATEMATIKA DALAM MENYELESAIKAN OPERASI HITUNG CAMPURAN BILANGAN BULAT PADA SISWA KELAS V SEKOLAH DASAR NEGERI 137 PEKANBARU - Siregar, Nurul Aisyah Amini; Fendrik, Muhammad; Zufriady (STKIP Subang, 2026)
This study aims to describe the mathematical literacy skills of fifth-grade students in solving mixed integer operation problems at SD Negeri 137 Pekanbaru. The research employed a qualitative descriptive approach with 24 students as the subjects. Data were collected through written tests based on mathematical literacy questions referring to AKM and interviews to explore students’ thinking processes. The results showed that most students were at the cognitive level of understanding, with a percentage of 86.1%, while only 20.8% of students were able to solve problems at the application level, and no students reached the reasoning level. The main difficulties experienced by students included interpreting contextual problems, identifying relevant information, and applying concepts of mixed integer operations accurately. Therefore, students’ mathematical literacy skills are still relatively low and have not developed to the reasoning stage. It is recommended that learning should emphasize strengthening basic concepts, continuous practice with literacy-based problems, and the development of higher-order thinking skills to improve students’ mathematical literacy optimally.